Interaction of Macroconomic Imbalances in Emerging Economies: The Case of Turkish Republics - (:unkn) unknown (AHMET YESEVI UNIV, 2017)
This study aims at analyzing macroeconomic imbalances and their interactions observed in emerging economies with a focus on the Turkic Republics. These countries have a special place in emerging economies because of their significant economic potentials. We used annual data covering the period of 2000-2014 of Azerbaijan, Kazakhstan, Kyrgyz Rebuplic, Tajikistan, Turkmenistan, Uzbekistan and Turkey. Panel VAR model and panel causality tests are applied as the method of analysis. The findings suggest that shocks arising from current account inconsistencies are highly likely to trigger a severe recession. It was also observed that current account shocks can significantly affect exchange rate misalignments as well. There is no strong evidence, however, that output gap and exchange rate misalignments have any serious effects both on each other and current account discrepancies.
Keywords: Macroeconomic imbalances; Turkish Republics; Vulnerabilities; Panel VAR; Panel Granger Test; CURRENT ACCOUNT IMBALANCES; MACROECONOMIC IMBALANCES; MONETARY-POLICY; EURO AREA; CYCLES